Efektivitas Teknik Latihan Asertif Untuk Meningkatkan Internal Locus Of Control Siswa dalam Belajar - Almuhaimin Sarnav Ituga (Program Studi bimbingan Konseling PPs UNM Makassar, 2017)
the objectives of the research are to discover (1) the description of the students’ internal locus of control in learning in class VIII at SMPN 5 Pasarwajo (2) the effectiveness of assertive training technique in improving the students’ internal locus of control in learning in class VIII at SMPN 5 Pasarwajo. The research was quasi experimental research which employed quantitative approach with pretest-posttest control group design. The measurement instrument were scale and observation. The data were analyzed by using descriptive statistics analysis and t-test. The results of the research reveal that (1) the levels of the students’ internal locus of control in learning in class VIII at SMPN 5 Pasarwajo before given the treatment it improves to high category, (2) Assertive training technique is effective to improve the students’ internal locus of control in learning in class VIII at SMPN 5 Pasarwajo.